Polymeric ruthenium( I) and binuclear ruthenium(1) and osmium(1) carboxylate-bridged complexes containing diphosphine, diarsine, arsinophosphine, diphosphine chalcogenide, and dithioether ligands: the structure of [Ru2( CO) 4( p-02CMe) 2( MeSCH2SMe)l2.THF - Steyn, Margo M. de V.; Hilts, Robert; Sherlock, Stephen J.; Cowie, Martin; Singleton, Eric (My University, 1990)
The addition of 1 molar equiv of the bidentate ligands L~L, R'2P(CH2)„PR'2, R'2As(CH2)„AsR'2, Ph2P(CH2)2AsPh2, Ph2PCH2P(S)Ph2, Ph2P(S)CH2P(S)Ph2, and R'SCH2SR' (R' = Me, Ph; = 1-4), to THF/acetone solutions of either the polymer [Ru2(CO)4(g-02CMe)2]ilor the dimers [Ru2(CO)40i-O2CR)2(NCMe)2] (R = Me, Et) affords a new class of polymeric species, [Ru2(CO)4(m-02CR')2(L L)]„, in which the carboxylate-bridged dimeric units are linked by the bidentate L~L ligands. The use of 2 molar equiv of either Ph2PCH2PPh2 (dppm) or Ph2PCH2P(S)Ph2 (dppmS) in the reaction with the acetate-bridged dimer yields complexes of the type [Ru2(C0)4(^-02CMe)2(7j1-Ph2PCH2P(X)Ph2)2] (X = S, electron pair). The osmium analogues [0s2(C0)4(u-02CMe)2(V-Ph2PCH2P(X)Ph2)2] can be obtained by heating [0$2(00)6(µ-020 ß)2] with 2 equiv of dppm or dppmS in CHCI3. The pendant PPh2 moieties of [0s2(C0)4(M-02CMe)2(7j1-dppm)2] can be oxidized to P(0)Ph2 groups by treatment with 2 molar equiv of H202. The structure of the dithioether species [Ru2(CO)40i-O2CMe)2(MeSCH2SMe)]2-THF has been determined by an X-ray diffraction study and has been shown to consist of a polymeric chain of [Ru2(C0)4(g-02CMe)2] units linked by MeSCH2SMe ligands. Each dimer unit has a sawhorse-like arrangement in which the four carbonyls are opposite the bridging acetate groups. The independent Ru-Ru bonds are 2.682 (1) and 2.684 (1) Á. This compound crystallizes in the space group P\ with a = 15.838 (2) A, b = 17.562 (2) A, c = 8.238 (2) A, a = 102.55 (l)°,/3 = 101.87 (1)°, = 68.17 (1)°, V = 2056.3 A3, and Z = 2. The asymmetric unit contains two [Ru2(C0)4(M-02CMe)2(MeSCH2SMe)] moieties. On the basis of 3533 unique observations and 435 parameters varied, the structure was refined to R = 0.046 and Rw = 0.055.